2022
DOI: 10.3390/biomedicines10102434
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sirtuins in Physiology and Diseases of the Central Nervous System

Abstract: Silent information regulators, sirtuins (SIRTs), are a family of enzymes which take part in major posttranslational modifications of proteins and contribute to multiple cellular processes, including metabolic and energetic transformations, as well as regulation of the cell cycle. Recently, SIRTs have gained increased attention as the object of research because of their multidirectional activity and possible role in the complex pathomechanisms underlying human diseases. The aim of this study was to review a cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 152 publications
0
12
0
Order By: Relevance
“…As such, NAD+ replenishment is emerging as a potential therapy to combat the development of neurological manifestations in diabetic subjects [ 21 ]. Insomuch as NAD+ acts as an obligatory coenzyme for a class of cellular protein deacetylases collectively known as sirtuins [ 11 ], the mechanisms underlying the anti-inflammatory effects by NAD+-increasing approaches may involve direct effects on such enzymes; however, the impact of NAD+-mediated deacetylation on NFκB signaling in brains of diabetic mice have not been addressed in any previous study. In this context, to our knowledge, our findings are the first to show the contribution of NAD+-related deacetylation mechanisms in the attenuation of brain inflammation and microglial activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, NAD+ replenishment is emerging as a potential therapy to combat the development of neurological manifestations in diabetic subjects [ 21 ]. Insomuch as NAD+ acts as an obligatory coenzyme for a class of cellular protein deacetylases collectively known as sirtuins [ 11 ], the mechanisms underlying the anti-inflammatory effects by NAD+-increasing approaches may involve direct effects on such enzymes; however, the impact of NAD+-mediated deacetylation on NFκB signaling in brains of diabetic mice have not been addressed in any previous study. In this context, to our knowledge, our findings are the first to show the contribution of NAD+-related deacetylation mechanisms in the attenuation of brain inflammation and microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…NAD+ depletion profoundly shapes the clinical outcome of diabetic brain inflammation [ 11 ]. As such, changes in NAD+ metabolism observed in diabetic subjects may reflect endogenous declines of NAD+ precursors (including NAM and their main related derivatives).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein deacetylase SIRT1 is the mammalian homolog of the yeast silent information regulator-2 (SIRT2), a member of the sirtuin family that has received considerable interest as a potential mediator of lifespan extension in a number of model animals. 48 In the clinical experiment of AD patients, RES reduces Aβ levels, improves brain volume, reduces the Mini-mental status score, and improves AD scores. [49][50][51] Furthermore, it is indicated that physiological doses of RES are safe and well tolerated.…”
Section: Re S and Al Zheimer ' S D Is E A S Ementioning
confidence: 99%
“…Notably, RES can also modulate different molecular pathways in neurodegenerative diseases by specifically activating silent information regulator‐1 (SIRT1). The protein deacetylase SIRT1 is the mammalian homolog of the yeast silent information regulator‐2 (SIRT2), a member of the sirtuin family that has received considerable interest as a potential mediator of lifespan extension in a number of model animals 48 …”
Section: Res and Alzheimer's Diseasementioning
confidence: 99%